'Eccellentissimo poeta et amatore divinissimo': Benedetto Varchi and Michelangelo's poetry at the Accademia Fiorentina. (July 2014) - Carlson, Raymond
<x content-type="archive" xml:space="preserve">Abstract</x> This study examines the first of two public lectures on Michelangelo delivered by Benedetto Varchi at the Accademia Fiorentina in 1547. The lecture played an unprecedented role in disseminating Michelangelo's poetry to a broad audience both orally and in print, and the article contends that Varchi was able to do so after receiving a manuscript of poems from an associate of Michelangelo in Rome. Varchi's broadcast of the poems has significant implications in relation to Michelangelo's rapport with Tommaso de' Cavalieri, who is named in the lecture as a recipient of Michelangelo's poetry. By upholding Michelangelo's enactment of Socratic love, Varchi grounds this Neoplatonic virtue in lived experience. Drawing on evidence including epistolary correspondence, archival sources, and Varchi's own poetry, the article shows why the Accademia would have been a uniquely receptive setting for the ideals espoused in Varchi's commentary.